2006
DOI: 10.2337/diacare.29.02.06.dc05-1626
|View full text |Cite
|
Sign up to set email alerts
|

Improving Metabolic Control Leads to Better Working Memory in Adults With Type 2 Diabetes

Abstract: OBJECTIVE -The goals of this study were to determine whether improvements in metabolic control can ameliorate the cognitive dysfunction associated with type 2 diabetes and evaluate the possibility that such improvements are mediated by changes in circulating insulin or insulin resistance. RESEARCH DESIGN AND METHODS -This randomized double-blind trial enrolled145 subjects at 18 centers in the U.S. Older adults with type 2 diabetes receiving metformin monotherapy received add-on therapy with either rosiglitazon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
154
2
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(172 citation statements)
references
References 48 publications
(22 reference statements)
6
154
2
3
Order By: Relevance
“…Recent clinical trials indicate that insulin-sensitizing drugs such as rosiglitazone improve cognition and memory in both AD and type 2 diabetes patients (28,43,50,51). The basis for the cognitive benefits of rosiglitazone has not been established, although reductions in inflammation and amyloid plaque burden have been hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials indicate that insulin-sensitizing drugs such as rosiglitazone improve cognition and memory in both AD and type 2 diabetes patients (28,43,50,51). The basis for the cognitive benefits of rosiglitazone has not been established, although reductions in inflammation and amyloid plaque burden have been hypothesized.…”
Section: Discussionmentioning
confidence: 99%
“…We had hypothesised that insulin-sensitising drugs such as metformin could be an addition to the armoury in the fight against cognitive decline. Indeed, others have found that a different class of insulin-sensitising agent (rosiglitazone), as well as the insulin secretagogue, glibenclamide (known as glyburide in the USA and Canada), significantly improve cognitive performance in patients with type 2 diabetes, and this improvement correlated with better control of fasting blood glucose [45]. There are studies currently underway to examine potential benefits of metformin on cognitive tasks in patients with type 2 diabetes and MCI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a cohort study on elderly females T2DM patients treated with oral hypoglycemic agents for 2 years showed no significant difference in their cognitive function as compared to nondiabetes populations (Logroscino et al, 2004). On the other hand, patient treatment for 6 months by rosiglitazone, a thiazolidinedione, or glyburide, a sulfonylurea combined with metformin showed improved FBG level and working memory (Ryan et al, 2006). Another study also found that oral hypoglycemic agents and multiple drug therapy were more effective at improving cognitive function than monotherapy (Wu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%